Sodium fluoride assisted acid leaching of coal fly ash for the extraction of alumina. (15th January 2019) - Tripathy, A.K.; Behera, B.; Aishvarya, V.; Sheik, A.R.; Dash, B.; Sarangi, C.K.; Tripathy, B.C.; Sanjay, K.; Bhattacharya, I.N.
Graphical abstract: Highlights: Coal fly ash was processed for the extraction of alumina. Extraction of alumina from fly ash was more efficient after removal of silica. Addition of sodium fluoride resulted in improving alumina leaching efficiency. A process flowsheet was developed for the extraction of alumina from fly ash. Abstract: Coal fly ash, generated in thermal power plants was processed through sulphuric acid leaching for the extraction of alumina. Both fly ash and alkali treated fly ash residue, obtained after partial removal of silica, were leached in sulphuric acid medium. Solubilisation of alumina in the acidic medium was found to be more efficient while processing the alkali treated fly ash residue as compared to the fly ash. The effect of addition of sodium fluoride (NaF) on leaching of alumina was examined at varied acid concentrations, temperatures, and time of leaching. A marked improvement in leaching recovery for alumina was observed due to the addition of NaF in the acidic leaching medium. XRD pattern of the leach residue confirmed that the alumina bearing phase i.e. mullite got dissociated in the presence of fluoride ions releasing alumina to the leaching medium for which a significant improvement in leaching efficiency was observed. A process flowsheet has been developed for the extraction of alumina from fly ash and production of a by-product, calcium silicate, for the regeneration of NaOH to make the process industrially viable.